Perlindungan Hukum Ahli Waris Dan Kreditur Persekutuan Komanditer Ketika Meninggalnya Sekutu Komplementer - Riky Rustam; Rizky Miraningsih (Fakultas Hukum Universitas Islam Indonesia, 2019)
This research is motivated by the conceptual conflict between civil inheritance law and company law in the form of commercial partnership (CV). The problems to be examined are first, the concept of legal protection of the rights of the heir to the complementary partner on the inheritance which has become a collateral for the debt of the CV, and second, the formulation of the concept of legal protection given to creditors of the CV for the death of the complementary partner whose heir is not willing to take responsibility for replacing their predecessor. The method used in this research is normative legal study by collecting library data. The results of this study concluded that first, the new complementary partner must be responsible for the debt of CV. Therefore, the new complementary partner must return the inheritance guarantee to the heir. Second, concurrent creditors must have a copy of the deed of CV to examine who is responsible if undesirable things happen in the CV, as a form of legal protection for themselves.